2015
DOI: 10.1186/s40317-015-0044-9
|View full text |Cite
|
Sign up to set email alerts
|

Tracking sharks without teeth: a non-invasive rigid tag attachment for large predatory sharks

Abstract: Background: Many marine species are difficult to study because components of their lifecycles occur solely or partially outside of the observable realm of researchers. Advances in biologging tags have begun to give us glimpses into these unobservable states. However, many of these tags require rigid attachment to animals, which normally requires catching and restraining the animals. These methods become prohibitive with large, dangerous, or rare species, such as large predatory sharks, and can have significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 16 publications
0
47
0
Order By: Relevance
“…Since ADLs must be firmly fixed to an animal to accurately record swimming movements, they cannot be quickly and easily attached with a pole-applicator without handling the animal, as can be done with satellite and acoustic tags in some cases. This increased handling time could lead to increased post-release mortality, although Campana et al (2015) found no difference between post-release mortality in mako sharks (Isurus oxyrinchus) pole-tagged in the water versus boat-landed, and quick, secure attachment of ADLs is available for some species (Gleiss et al, 2009;Chapple et al, 2015).…”
Section: Applicationsmentioning
confidence: 99%
“…Since ADLs must be firmly fixed to an animal to accurately record swimming movements, they cannot be quickly and easily attached with a pole-applicator without handling the animal, as can be done with satellite and acoustic tags in some cases. This increased handling time could lead to increased post-release mortality, although Campana et al (2015) found no difference between post-release mortality in mako sharks (Isurus oxyrinchus) pole-tagged in the water versus boat-landed, and quick, secure attachment of ADLs is available for some species (Gleiss et al, 2009;Chapple et al, 2015).…”
Section: Applicationsmentioning
confidence: 99%
“…However, these tags have yet to reach widespread use on large, highly mobile marine species such as sharks and other top predators, because of the challenge of recovering loggers from animals that can cover large distances quickly and are difficult or impossible to recapture. A few previous studies have described data logger float package attachment mechanisms for use on large sharks, including whale sharks (Rhincodon typus, [22]), Greenland sharks (Somniosus microcephalus, [23]), tiger sharks (Galeocerdo cuvier, [24]), and white sharks (Carcharodon carcharias, [25]). However, these studies employed small sample sizes or used sharks that were generally known to remain within a recognized area or were tracked for the duration of the deployment to facilitate logger recovery.…”
Section: Introductionmentioning
confidence: 99%
“…These factors led to the inclusion of several species of batoids in the IUCN Red List of Threatened Species (http://www.iucnssg.org), which have demanded different conservation measures (Dulvy et al ., ). These measures include the development and improvement of methods and techniques based on non‐lethal approaches (thereby improving animal welfare while gaining the trust and support of wildlife stakeholders (Hammerschlag et al ., )), such as baited remote underwater video systems (Sherman et al ., ), electronic tagging (Chapple et al ., ; Fontes et al ., ), and genetics (Domingues et al ., ).…”
Section: Pairwise Genetic Distance Using Kimura‐two‐parameter Model Omentioning
confidence: 98%